The influence of behavioural economic on spending patterns in digital payment systems empirical evidence from Germany - Alsaloom, Rifaat (2025)
Fil: Alsaloom, Rifaat. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.